1984
DOI: 10.1063/1.333010
|View full text |Cite
|
Sign up to set email alerts
|

Stress effect in Au-Si Schottky diode doped with Cu

Naotake Tōyama

Abstract: The stress effect in Au-Si Schottky diodes doped with copper was examined by photoelectric measurement under localized anisotropic stress of the order of 109 dyn/cm2. It was found out that the current increase with stress was due to the changes of both the shunt resistance and the effective Richardson constant of a Schottky diode. The changes of these diode parameters with stress are attributed to the multiplication of the residual lattice strain in silicon due to copper introduction. The lattice strain produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…In particular, the electronic properties of gold-silicon compounds and interfaces have been studied, 1 including the measurement of Schottky diode barrier behavior in copper doped Au-Si films. 2 Evidence for the existence of metastable Au-Si structures at gold-silicon interfaces has also been obtained. 3 In one high resolution TEM study, spherical Au-Si nanoclusters were observed under certain annealing conditions.…”
Section: Introductionmentioning
confidence: 83%
“…In particular, the electronic properties of gold-silicon compounds and interfaces have been studied, 1 including the measurement of Schottky diode barrier behavior in copper doped Au-Si films. 2 Evidence for the existence of metastable Au-Si structures at gold-silicon interfaces has also been obtained. 3 In one high resolution TEM study, spherical Au-Si nanoclusters were observed under certain annealing conditions.…”
Section: Introductionmentioning
confidence: 83%